Pengalaman Perempuan dengan Unmet Need dalam Pengambilan Keputusan Penggunaan Kontrasepsi di Jombang: Studi Fenomenologi - Eka Rahmaningrum; Dwi Izzati Budiono; Lilik Djuari; Ratna Dwi Jayanti (Yayasan Jompa Research and Development, 2026)
Unintended pregnancies increase the risk of maternal mortality and stunting due to suboptimal family planning and a high prevalence of unmet need for modern contraception. The prevalence of unmet need in Indonesia is 5.22% and 9.25% in Jombang Regency in 2023. This study aimed to explore women’s experiences in decision-making regarding contraceptive use in Jombang. Method: This qualitative research employed a phenomenological design. Data were collected through in-depth interviews with six women experiencing unmet need for modern contraception, selected using purposive sampling based on inclusion and exclusion criteria. Data were analyzed using Cresswell’s thematic analysis. Results: Decision-making was influenced by considerations related to modern contraception, including concerns about side effects, comfort, cultural and religious norms, access to information, and partner dominance in decision-making. Furthermore, traditional methods were chosen as a strategy to space pregnancies because they were perceived as safer, more convenient, aligned with personal beliefs, and supported by husbands despite the higher risk of failure. Conclusion: Family planning decision-making is shaped by reproductive experiences, cultural values, access to information, and partner involvement. Empathetic counseling and partner engagement are essential to improve the use of modern contraceptive methods.